Gambaran Jumlah Leukosit pada Penderita Demam Berdarah Dengue di Klinik DR.Trisna Garut - Agung Erwin Mulyadi; Agus Sudrajat (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Dengue hemorrhagic fever (DHF) is a public health problem in Indonesia whose number of cases continues to increase and its spread is increasingly widespread.Tests used to diagnose dengue fever include a white blood cell count test.White blood cells are cells that play a role in the body's defense system. The reason is, white blood cells help fight infections in the body, such as viruses, bacteria, parasites and fungi. In patients infected with dengue fever, the white blood cell count is usually normal but then decreases (leukopenia) and neutropenia becomes dominant. Thisresearch was conducted from March to April 2023.The aim of this study was to measure the number of white blood cells in dengue fever patients.This type of research is descriptive. The research was carried out using an automatic analysis method (blood analysis) in the laboratory ofKlinik Dr.Trisna Garut, using samples from 30 dengue fever patients who were tested. In this study, the number of white blood cells in dengue fever patients at Klinik Dr.Trisna Garut was 14 (46.7%).Wich is Normal And the white blood cell count results of dengue fever patients at Klinik Dr.Tisna Garut General Hospital decreased by 16 (54.3%).